IMPROVING FINANCIAL MECHANISMS FOR DECARBONIZATION OF GAS INFRASTRUCTURE IN THE TRANSITION TO A GREEN ECONOMY - Qulliyev Ulug’bek Mirzayevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study proposes a performance-based financial mechanism for decarbonizing Uzbekistan’s gas transport infrastructure. Using the Mubarek Compressor Station case, the model combines grant financing, verified gas savings, escrow accumulation, and reinvestment. Findings show that targeted methane reduction measures can generate rapid economic returns and support green transition goals.